2022
DOI: 10.3389/fpsyg.2022.823647
|View full text |Cite|
|
Sign up to set email alerts
|

Absence of Behavioral Harm Following Non-efficacious Sexual Orientation Change Efforts: A Retrospective Study of United States Sexual Minority Adults, 2016–2018

Abstract: BackgroundDo sexual minority persons who have undergone unsuccessful sexual orientation change efforts (SOCE) suffer subsequent psychological or social harm from the attempt? Previous studies have conflated present and past, even pre-SOCE, harm in addressing this question. This study attempts, for the first time, to isolate and examine the question of current psychosocial harm for former SOCE participants among sexual minorities in representative population data.MethodUsing nationally representative data (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The risk of harm behaviors for those who have experienced SOCE is no different than it is for those who have not experienced SOCE. SOCE experience was found to have no statistically discernible effect on the risk of any present harm measured in terms of suicide ideation, suicide planning, suicide intention, and attempting suicide (Sullins, 2022). Other research is based on self-reports, which is the same type of method they accuse as invalid for supporting SOCE.…”
Section: Ethical and Professional Concernsmentioning
confidence: 96%
See 3 more Smart Citations
“…The risk of harm behaviors for those who have experienced SOCE is no different than it is for those who have not experienced SOCE. SOCE experience was found to have no statistically discernible effect on the risk of any present harm measured in terms of suicide ideation, suicide planning, suicide intention, and attempting suicide (Sullins, 2022). Other research is based on self-reports, which is the same type of method they accuse as invalid for supporting SOCE.…”
Section: Ethical and Professional Concernsmentioning
confidence: 96%
“…At the same time, if one were to study SOCE experience among non-religious persons who currently identify strongly as lesbian or gay and probably did so before or during SOCE, or who engaged in SOCE due to external pressures rather than on their own volition, one can expect to find far more negative results and more frequent reports of harm. However, when compared in research, sexual minority persons who had undergone failed SOCE therapy do not suffer higher psychological or social harm (Sullins, 2022).…”
Section: Soce and Risks Of Harmmentioning
confidence: 99%
See 2 more Smart Citations
“…Using data from Generations —a study of a nationally representative sample of sexual minority adults—Blosnich et al ( 2020 ) found that exposure to sexual orientation change effort (SOCE or “conversion therapy”) was associated with twice the odds of lifetime suicidal ideation, 75% increased odds of planning to attempt suicide, and 88% increased odds of a suicide attempt with minor injury compared with people with no history of being exposed to SOCE. Sullins ( 2022 ) raised several critiques of that study, including that it did not time the occurrence of SOCE in relation to suicidality, making it difficult to determine the causality, and that it did not sufficiently control for potential confounders of suicidality. Using the Generations data, Sullins attempted to address these limitations, but his solutions are flawed, rendering his conclusions invalid.…”
Section: Introductionmentioning
confidence: 99%